Treatment persistence and colectomy-free outcomes in patients with ulcerative colitis receiving golimumab or adalimumab: a UK experience. Issue 1 (16th November 2020) - Hoque, Sami; Puenpatom, Amy; Boccaletti, Simona; Green, Chloe; Black, Christopher M; Roberts, Jenna; Rajkovic, Ivana; Milligan, Gary
Abstract : Objective: To examine real-world treatment persistence, colectomy-free survival and treatment switching patterns in UK patients with ulcerative colitis (UC) prescribed golimumab or adalimumab. Design: This was a retrospective chart review study in adult patients diagnosed with UC using data from 16 National Health Service sites in the UK. Patient records were included in the study if they had initiated first or second-line adalimumab or golimumab between 1 March 2016 and 30 September 2017 (index date). Subjects were required for ≥6 months post treatment initiation. Demographics, clinical characteristics, treatment-related data and colectomy data were extracted over a follow-up period of 6–12 months. Treatment persistence rate was the primary outcome. Colectomy-free survival and treatment switching were secondary outcomes. Outcomes were compared between treatments using χ 2 tests and Fisher's exact test for categorical variables. The t-tests were used for continuous variables. Time-to-event variables were evaluated using Kaplan-Meier curves and log-rank tests. Results: The study included a total of 183 patients (96 (52.5%) prescribed adalimumab; 87 (47.5%) golimumab), and patients were mostly first line (79.8%). Demographic and clinical characteristics were generally similar between treatment groups. Persistence rates within 12 months were 64.6% for adalimumab and 64.4% for golimumab (p=0.681). Overall, 20.2% switched to other therapy within 1 year, with 8.2% golimumab and 12.0% adalimumab switching to another biologic. Of patients prescribed adalimumab, 14.6% had ≥1 dose change, mainly dose escalations. In the 12 months post treatment initiation, 8.2% of patients underwent colectomy, with no significant difference in colectomy-free survival by treatment, p=0.73. Conclusion: This study provides evidence of clinical outcomes and real-world persistence for adalimumab and golimumab in UC. The persistence rates of both therapies were above 64.0% at 12 months following treatment initiation. In addition, the 1-year colectomy-free survival was relatively similar between the two treatments.